STRATEGI PENGEMBANGAN KINERJA KARYAWAN - Gunawan, Surtono; Widyastuti, Sri; Gustari , Irvandi (SEKOLAH PASCASARJANA PRESS, 2018)
In almost all existing companies, especially companies engaged in financial services, employees is an important asset that must be maintained because they rely on the performance level of employees in the company, then the company is required to be able to optimize the performance of its employees. Motivation, job satisfaction, work status and organizational commitment at this critical time in managing employees to be more productive. This study addressed the problem of how much influence employee motivation on employee performance ?, How much influence job satisfaction on employee performance ?, how much influence the employment status of the employee's performance? Is organizational commitment mediate the relationship between motivational influence on employee performance? Is organizational commitment mediate the relationship between job satisfaction influence on employee performance? Is organizational commitment mediate the relationship between employment status influence on employee performance? The method used is descriptive and explanative, engineering data collection is done by giving questionaire to 100 employees in the business team and analyzed using Structural Equation Model (SEM) Smart PLS. With census data collection techniques to employees.